2015
DOI: 10.1093/nar/gkv1353
|View full text |Cite
|
Sign up to set email alerts
|

Linc-RoR promotes c-Myc expression through hnRNP I and AUF1

Abstract: Linc-RoR was originally identified to be a regulator for induced pluripotent stem cells in humans and it has also been implicated in tumorigenesis. However, the underlying mechanism of Linc-RoR-mediated gene expression in cancer is poorly understood. The present study demonstrates that Linc-RoR plays an oncogenic role in part through regulation of c-Myc expression. Linc-RoR knockout (KO) suppresses cell proliferation and tumor growth. In particular, Linc-RoR KO causes a significant decrease in c-Myc whereas re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
97
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(102 citation statements)
references
References 40 publications
4
97
1
Order By: Relevance
“…What's more, in nasopharyngeal carcinoma, linc-ROR played an important role in the progression of NPC and the mechanism by which NPC resists chemotherapy might be that linc-ROR suppress p53 signal pathway [76]. Similar to this pathway, the linc-ROR also plays an oncogenic role in regulating the c-Myc (enhancing its mRNA stability) by interacting with hnRNP I and AU-rich element RNA-binding protein 1 (AUF1) [77,78]. Moreover, the nuclear factor-crythroid 2-related factor (NRF2), which is activated under high cellular stress and is well established as a master regulator in cellular defensing against chemical carcinogenesis [79,80], directly binding linc-ROR promoter and represses its expression [81].…”
Section: Linc-ror Plays An Important Role For the Cell To Better Respmentioning
confidence: 99%
See 1 more Smart Citation
“…What's more, in nasopharyngeal carcinoma, linc-ROR played an important role in the progression of NPC and the mechanism by which NPC resists chemotherapy might be that linc-ROR suppress p53 signal pathway [76]. Similar to this pathway, the linc-ROR also plays an oncogenic role in regulating the c-Myc (enhancing its mRNA stability) by interacting with hnRNP I and AU-rich element RNA-binding protein 1 (AUF1) [77,78]. Moreover, the nuclear factor-crythroid 2-related factor (NRF2), which is activated under high cellular stress and is well established as a master regulator in cellular defensing against chemical carcinogenesis [79,80], directly binding linc-ROR promoter and represses its expression [81].…”
Section: Linc-ror Plays An Important Role For the Cell To Better Respmentioning
confidence: 99%
“…So, p53, NRF2, linc-ROR and c-Myc may form a regulatory network upon DNA damage, the high expression of p53 inhibits the activation of NRF2, which leading to the upregulation of linc-ROR, as a result, the high expression of linc-ROR can supress the p53 level, at the same time inhibit the expression of c-Myc by interacting with hnRNP I and AUF1 [74,77,81]. This forms a feeback loop which confirms the importance of linc-ROR in playing an oncogenic role.…”
Section: Linc-ror Plays An Important Role For the Cell To Better Respmentioning
confidence: 99%
“…Evidence suggests it acts as a microRNA sponge of miR-145, which is a repressor of the core pluripotency transcription factors Oct4, Nanog and Sox2 [146]. Several recent studies have reported an oncogenic role for Linc-ROR in different cancers by sponging miR-145 [147–149] or through other mechanisms [150, 151]. …”
Section: Introductionmentioning
confidence: 99%
“…28 Linc-RoR functions as a decoy oncogenic RNA to impede the recruitment of G9A methyltransferase, abolishing histone H3K9 modification of the TESC promoter to promote tumor development. 29 After DNA damage, the level of p53 that can suppress tumor is noticeably increased; this increase is regulated in various ways, including translational control. 29 After DNA damage, the level of p53 that can suppress tumor is noticeably increased; this increase is regulated in various ways, including translational control.…”
Section: Discussionmentioning
confidence: 99%